PENERAPAN HUKUM PIDANA PADA TINDAK PIDANA GRATIFIKASI YANG DILAKUKAN DALAM JABATAN (Studi Kasus Putusan Nomor 1/Pid.Sus.TPK/2017/PN.Mdn) - Atozanolo Baene (Jurnal Panah Hukum, 2022)
The State of Indonesia is a constitutional state as stipulated in Article 1 paragraph (3) The 1945 Constitution of the Republic of Indonesia. Therefore, all citizens must submit and obey the applicable law. Gratification is a gift in a broad sense, namely the gift of money or goods. This research was conducted to find out and analyze the application of criminal law to gratuity crimes committed in office (Case Study of Decision Number 1/Pid.Sus.TPK/2017/ PN.Mdn). The criminal act of gratification is an unlawful act that is bribery in nature, namely the element of the act of promising something even though the promise has not been received, as well as giving a gift is considered to have occurred after the object was released from the power to give. This research is normative legal research using statutory regulations, case approaches, and analytical approaches. Data collection was carried out using secondary data obtained through literature study consisting of primary legal materials, secondary legal materials and tertiary legal materials. Data analysis used is qualitative analysis. Based on the results of the research and discussion on the application of criminal law to criminal acts of gratification committed in office (Case Study of Decision Number 1/Pid.Sus.TPK/2017/PN.Mdn), it can be concluded that the panel of judges in deciding cases in District Court decisions Medan Number 1/Pid.Sus.TPK/2017/PN.Mdn, there was an error in applying Article 11 because it was in accordance with the fact that the defendant's actions violated the provisions of Article 12 b of the Law of the Republic of Indonesia Number 20 of 2001 concerning Amendments to the Law Republic of Indonesia Number 31 of 1999 concerning Eradication of Corruption as referred to in the subsidiary indictment. As for the suggestion in this study is that law enforcers, in this case judges, should be more careful and thorough in applying the law to the perpetrators according to their actions